PENGARUH KOMPLEKSITAS OPERASI, KONTINJENSI, PERGANTIAN AUDITOR PADA AUDIT REPORT LAG DENGAN SPESIALISASI AUDITOR SEBAGAI PEMODERASI - Dewi, Gusti Ayu Nyoman Purnama; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 21 No 2 (2017)DO - 10.24843/EJA.2017.v21.i02.p02, 2017)
T his study aim s to examine the effect of the operation’s complexity , contingency, auditor change on the audit report lag with auditor specialization as moderating variable. The population are property and real estate compan ies that have been listed in the Indonesia Stock Exchange (BEI) on the period 2012-2015. The sample of 32 companies with 128 observations determined using purposive sampling method. This research uses secondary data which was determined by using non participant observation method. The data analysis technique is a multiple regression analysis that uses Moderated Regression Analysis test. The results show s the operation’s complexity and contingenc y have positive influence to cause a longer audit report lag , while auditor change has no effect on audit report lag. A uditor s pecialization is able to weaken the effect of contingency on audit report lag. A uditor s pecialization is weaken the effect of contingency reporting which resulting in a shorter audit report lag .
Keywords: audit report lag, complexity of operation, contingency, auditor change, auditor specialization